The research on various factors’ influence on M&A transaction price - Stukas, Dovydas; Miečinskienė, Algita (Business: Theory and Practice, 2010)
Mergers and acquisitions (further – M&A) are undoubtedly one of the most rapid ways to expand or enter into a new market. It is widely discussed how complex and sophisticated the processes of merger or acquisition are, so they cannot be executed without supervision of professional consultants, lawyers and accountants. Every transaction comprises many internal and external factors which have influence on the final price of M&A deal. The aim of this paper is to find out the importance level of various factors affecting M&A transaction price. Thorough research on 22 different factors has been carried out. All respondents were closely related to M&A transaction process. They were asked to specify how important, in their opinion, each factor for M&A transaction price was. The results show that the most important factors are financial state of a company, future growth prospects and sales profitability. It is solidly admitted that the least weight on M&A transaction price is given according to official financial analysts: research on company stocks, success on the stock market and “windows dressing“ before putting a company on sale. It was also noticed, that the rating of these factors depends on respondents’ experience and position in job.On the basis of the results, first and middle level managers concentrate more on financial factors and process execution, while the top-level managers deal with strategic matters.Article in Lithuanian.Įmonių susijungimų ir įsigijimų sandorių kainai įtaką darančių veiksnių tyrimasSantrauka. Straipsnio tikslas – ištirti mikro- ir makroaplinkos veiksnių svarbą įmonių susijungimų ir įsigijimų sandorių kainoms. Atlikus Lietuvos ir užsienio autorių mokslinių straipsnių bei kitų šaltinių analizę nagrinėjama tema, išskirtos tokios mikro- ir makroaplinkos veiksnių, formuojančių sandorių kainą, grupės: politiniai, socialiniai, ekonominiai, rinkos, finansiniai veiksniai. Šias grupes nagrinėjant išsamiau, atrinkti 22 veiksniai, kurie pateikti respondentams, dirbantiems finansų, investavimo, konsultavimo ir kitoje su susijungimais bei įsigijimais susijusioje srityje, vertinti. Atlikus tyrimą nustatyta, kad didžiausią įtaką sandorių kainoms turi tokie veiksniai, kaip finansinė įmonės padėtis, augimo potencialas ir pardavimo pelningumas. Mažiausią įtaką kainai turi tokie tirti veiksniai, kaip viešos analitikų rekomendacijos akcijoms, listingavimas biržoje, verslo rodiklių pagražinimas prieš sandorį. Taip pat ištirta, kad didžiausią įtaką susijungimų ir įsigijimų sandorių kainą veikiančių veiksnių svarbos suvokimui turi respondentų darbo patirtis ir užimamos pareigos.Reikšminiai žodžiai: susijungimai, įsigijimai, verslo pardavimas, verslo vertė, vertinimas, sandorio kaina.